EMPLOYER BRANDING PT. ASTRA INTERNASIONAL - Arianis Chan; Rivani .; Siti Fajarwati Azzahra (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2019)
This study aims to analyze the implementation of employer branding implemented by PT Astra International. The research method used in this study is a qualitative method with descriptive type. The object of this research is Employer Branding. The results of the study provide information that innovation is the main key for PT. Astra International to survive in this competitive era, innovation is always supported by companies. Support is provided through the provision of innovation development platforms in the form of internal competition. In addition to the employer branding program implemented through internal employees, the employer branding program in the education pillar is carried out not only for universities, but also for all levels of education. The conclusion of this study is Employer Branding at PT. Astra International is implemented seriously and deeply because of the goals of the company's Employer Branding. PT Astra International has a strategic framework of